To resect or not to resect: a review of pancreatic cyst disease management. Issue 5 (September 2018) - Harrison, Jon M.; Castillo, Carlos Fernandez-del
Abstract : Purpose of review: With recent advances in radiographic testing, there have been increases in the incidental identification of pancreatic cysts. Determining management, specifically, which cysts can be watched versus intervened upon has significant impact on at the patient–physician level as well as globally on resource allocation and healthcare expenditures. This review focuses on the three main guidelines (Fukuoka guidelines, European consensus, and American Gastroenterological Association recommendations) for management of pancreatic cystic disease after incidental identification. Recent findings: There are iterant revisions to each set of recommendations every few years as new data is published on the subject. This review encompasses the most up-to-date recommendations for management while also providing a framework for conceptualizing work-up for varying types of pancreatic cystic disease before and after incidental identification. Summary: Pancreatic cystic disease should be approached in thoughtful clinical manner, and each cyst should be evaluated in the context of patient's health and healthcare goals. All cysts, however, should be considered malignant until proven otherwise. Applications of different diagnostic modalities like MRI and EUS with FNA can better characterize cystic lesions and assess malignant potential. Resection should always be considered in cysts with concerning features. If deferred, surveillance should be continued indefinitely. Early termination of surveillance risks future malignant progression.